Mengoptimalkan Akurasi pada Klasifikasi Emosi Majemuk Berdasarkan Semantik Kalimat Menggunakan XLM-RoBERTa - Aripin; Steven Adi Santoso; Hanny Haryanto (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2023)
There are six basic emotions; they are anger, sadness, happiness, disgust, surprise, and fear. A combination of basic emotions creates a new type of emotion called a compound emotion. The examples of applying these compound emotions are in chatbots, translations, and text summarization. Several research on classifying these emotions based on Indonesian texts have used traditional models such as multinomial naïve Bayes, support vector machine (SVM), k-nearest neighborhood, and term frequency–inverse document frequency (TF-IDF). The previous research have a massive drawback, primarily on their less optimized performances. The models used could only classify things with the available data; thus, the text processing is required that results in a longer training time for larger This research aims to solve the issue from the previous research by using cross-lingual language model-robustly optimized bidirectional encoder representations from transformers approach (XLM-RoBERTa) model to classify compound emotions based on the semantics or meaning in words and sentences. The XLM-RoBERTa is a transformer model that can identify the meaning of a word from its attention mechanism and represent it as a vector to know the usage and position in a sentence. It is also a method to understand the meaning of a specific word. Using the attention mechanism, the model used the word position to recognize the sentence pattern and classify them even further to know the pattern and sequence to understand the semantics. The experiment result showed that the model could classify Indonesian texts into basic and compound emotion classes with an accuracy of up to 95.56%. This result is much higher than using traditional models to classify the compound emotion classes.